Production of banana 'Prata Anã' under potassium and magnesium fertilizations in an area irrigated with limestone in the locality of Januária - MG. (Research, Society and Development, 2020)
The present work aimed to determine the effects of the application of K and Mg on the vegetative and productive development of the banana 'Prata Anã' (Musa spp.) irrigated with alkaline water from an underground aquifer. The experiment was conducted in the fruit sector of the IFNMG-Campus Januária. The doses of 5, 10, 15, 20 and 30 g / family per month were tested with magnesium sulfate; and 20, 40, 60, 80 and 120 g / family per month with potassium chloride combined by the experimental Double Square matrix (incomplete); and a witness with omission in the supply of potassium and magnesium fertilizers. The characteristics of vegetative development (circumferences at 0.3 and 1.3 m in height of the pseudostem) and productive (mass of clump, mass of the second clump, number of fruits of the second clump, number of fruit per cluster, number of bunches per bunch, mass of the central fruit, length and diameter of the central fruits of the 2nd bunch and stalk mass). The evaluated characteristics, number of clumps and length of the three central fruits of the second clump were not significantly affected by the applied doses of fertilizers K and Mg. The estimates of maximum fertilizer efficiency occurred when combining the following doses of MgSO4 fertilizer with 120 g of KCl for most of the evaluated characteristics. The linear models for the potassium chloride factor indicate the need for further research in order to determine inflection points for this fertilizer for the characteristics evaluated in the present work.